2011
DOI: 10.1103/physreve.84.056104
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-dynamics simulation of clustering processes in sea-ice floes

Abstract: In seasonally ice-covered seas and along the margins of perennial ice pack, i.e., in regions with medium ice concentrations, the ice cover typically consists of separate floes interacting with each other by inelastic collisions. In this paper, hitherto unexplored analogies between this type of ice cover and two-dimensional granular gases are used to formulate a model of ice dynamics at the floe level. The model consists of (i) momentum equations for floe motion between collisions, formulated in the form of a S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 33 publications
0
63
0
Order By: Relevance
“…Previous experiments with an earlier version of the model demonstrated that polydispersity plays an important role in many aspects of the dynamics of sea ice composed of floes with power-law size distribution, including the formation of clusters in response to wind [19,20]. Not surprisingly, polydispersity also influences the behavior of the sheared systems studied here.…”
Section: The Role Of Polydispersitymentioning
confidence: 50%
See 2 more Smart Citations
“…Previous experiments with an earlier version of the model demonstrated that polydispersity plays an important role in many aspects of the dynamics of sea ice composed of floes with power-law size distribution, including the formation of clusters in response to wind [19,20]. Not surprisingly, polydispersity also influences the behavior of the sheared systems studied here.…”
Section: The Role Of Polydispersitymentioning
confidence: 50%
“…This work is a continuation of previous numerical studies on sea ice composed of disk-shaped floes with power-law size distribution [19][20][21]. It examines the behavior of a 2D polydisperse granular material composed of frictional grains under pure-shear deformation (constant packing fraction, or, in the sea-ice nomenclature, ice concentration A).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some, like neXtSIM, treat the sea ice as a continuous medium, but with different rheologies (e.g. Coon et al (1974) and Hibler III (1979) modelled sea ice as an elasto-plastic material; Hunke and Dukowicz (1997) as an elasto-visco-plastic material; and Dansereau (2016) as an Maxwell elasto-brittle material), and are suitable for high ice concentration (> 80 %), while others that treat the ice as a discrete medium (Hopkins et al, 2004;Wilchinsky et al, 2010;Herman, 2011;Rabatel et al, 2015) are more suitable for low ice concentration (< 80 %) such as within the marginal ice zone.…”
Section: Introductionmentioning
confidence: 99%
“…Some, like neXtSIM, treat the sea ice as a continuous medium, yet with different rheologies (e.g. visco-plastic (Coon et al, 1974;Hibler III, 1979), elasto-visco-plastic, (Hunke and Dukowicz, 1997), or Maxwell-elasto-brittle, (Dansereau, 2016)), are suitable 10 for high ice concentration (> 80%) while others, that treat the ice as a discrete medium (Hopkins et al, 2004;Wilchinsky et al, 2010;Herman, 2011;Rabatel et al, 2015), are more suitable for low ice concentration (< 80%) such as within the marginal ice zone.…”
mentioning
confidence: 99%